Clinically Important Phleboviruses and Their Detection in Human Samples - Lambert, Amy J.; Hughes, Holly R. (Viruses, 2021)
The detection of phleboviruses (family: Phenuiviridae) in human samples is challenged by the overall diversity and genetic complexity of clinically relevant strains, their predominantly nondescript clinical associations, and a related lack of awareness among some clinicians and laboratorians. Here, we seek to inform the detection of human phlebovirus infections by providing a brief introduction to clinically relevant phleboviruses, as well as key targets and approaches for their detection. Given the diversity of pathogens within the genus, this report focuses on diagnostic attributes that are generally shared among these agents and should be used as a complement to, rather than a replacement of, more detailed discussions on the detection of phleboviruses at the individual virus level.